Agricultural extension reforms in South Asia : status, challenges, and policy options - Babu, Suresh Chandra; Joshi, P. K. (Academic Press, an imprint of Elsevier, 2019)
Agricultural Extension Reforms in South Asia: Status, Challenges, and Policy Options is based on agricultural extension reforms across five South Asian countries, reflecting past experiences, case studies and experiments. Beginning with an overview of historical trends and recent developments, the book then delves into country-wise reform trajectories and presents several cases testing the effectiveness of different types (public and private) and forms (nutrition extension, livestock extension) of extension systems. Further, the book provides a comprehensive overview of challenges and constraints faced in formulating and implementing reforms, tying the results into a concrete set of lessons and highlighting areas that require further research. In addition, the book discusses how a major aspect of agricultural development is the productivity increase from the knowledge base of farmers, and how translating research results into a knowledge base for farmers requires designing and implementing well-functioning extension programs.